Uso de alineadores dentales invisibles en pacientes con clase II de Angle - Moposita Yanchatipán, Tannia Alexandra (2023)
ABSTRACT: They are transparent plates that cover the crowns of the dental pieces and are anchored by means of attachments to control orthodontic movements. They are extracted from the oral cavity to eat and during tooth brushing, which is why their use is recommended for 22 hours; they treat simple cases faster but can also treat complex cases with extractions and surgeries as occurs in Angle class II and III. In this study, the use of invisible aligners in Angle class II was analyzed, all the information was obtained from scientific databases such as Google Scholar, PubMed, Researchgate, Elsevier, Scielo, MPDI, Hidwani, KoreaMed, in the period from 2012 to 2022, based on the review of 63 articles. The results showed that invisible aligners are currently taken as an orthodontic treatment with high demand for the esthetic part, avoiding the use of traditional orthodontics. It was determined that Angle class II subdivision 1 has a greater use with Angle class I bite. It is concluded that treatment with invisible aligners, being removable plates, can treat all types of malocclusions, such as Angle class II subdivision 1, which is very successful, improving esthetics, periodontal health, dental hygiene and reducing pain during treatment; with better results in a shorter time compared to conventional treatment.